Adaptation to Endoplasmic Reticulum Stress in Candida albicans Relies on the Activity of the Hog1 Mitogen-Activated Protein Kinase - Husain, Farha; Pathak, Prerna; Román, Elvira; Pla, Jesús; Panwar, Sneh Lata (Frontiers in Microbiology, 2022)
Adaptation to ER stress is linked to the pathogenicity of C. albicans. The fungus responds to ER stress primarily by activating the conserved Ire1-Hac1-dependent unfolded protein response (UPR) pathway. Subsequently, when ER homeostasis is re-established, the UPR is attenuated in a timely manner; a facet that is unexplored in C. albicans. Here, we show that C. albicans licenses the HOG (high-osmolarity glycerol) MAPK pathway for abating ER stress as evidenced by its activation and translocation to the nucleus during tunicamycin-induced ER stress. We find that, once activated, Hog1 attenuates the activity of Ire1-dependent UPR, thus facilitating adaptation to ER stress. We use the previously established assay, where the disappearance of the UPR-induced spliced HAC1 mRNA correlates with the re-establishment of ER homeostasis, to investigate attenuation of the UPR in C. albicans. hog1Δ/Δ cells retain spliced HAC1 mRNA levels for longer duration reflecting the delay in attenuating Ire1-dependent UPR. Conversely, compromising the expression of Ire1 (ire1 DX mutant strain) results in diminished levels of phosphorylated Hog1, restating the cross-talk between Ire1 and HOG pathways. Phosphorylation signal to Hog1 MAP kinase is relayed through Ssk1 in response to ER stress as inactivation of Ssk1 abrogates Hog1 phosphorylation in C. albicans. Additionally, Hog1 depends on its cytosolic as well as nuclear activity for mediating ER stress-specific responses in the fungus. Our results show that HOG pathway serves as a point of cross-talk with the UPR pathway, thus extending the role of this signalling pathway in promoting adaptation to ER stress in C. albicans. Additionally, this study integrates this MAPK pathway into the little known frame of ER stress adaptation pathways in C. albicans.